(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To improve oral bioavailability of curcumin by a combination of approaches. Materials and Methods: Liposomes were prepared by thin film hydration method. Prepared liposomes were evaluated for its physical characteristics such as particle size, zeta potential, and encapsulation efficiency. Release study and bioavailability was also determined on rat. Blood samples were collected at specific intervals, and plasma was separated by ultracentrifugation. Plasma was analyzed by high-performance liquid chromatography at 420 nm taking acetic acid:acetonitrile (9:1) ratio as a mobile phase at a flow rate of 0.5 ml/min using C18 column. Result and Discussion: Increase in zeta potential indicates more uniform size distribution. From in-vivo study, it is clear that liposomal curcumin and piperine increases Cmax, area under the curve, and mean residence time significantly as compared to other approaches. Conclusion: Oral bioavailability of curcumin can be significantly increased by combining two approaches. The single approach may not be sufficient to overcome the hindrance of curcumin.